2014
DOI: 10.3389/fpsyg.2014.00253
|View full text |Cite
|
Sign up to set email alerts
|

The ties to unbind: age-related differences in feature (un)binding in working memory for emotional faces

Abstract: In the present study, we investigated age-related differences in the processing of emotional stimuli. Specifically, we were interested in whether older adults would show deficits in unbinding emotional expression (i.e., either no emotion, happiness, anger, or disgust) from bound stimuli (i.e., photographs of faces expressing these emotions), as a hyper-binding account of age-related differences in working memory would predict. Younger and older adults completed different N-Back tasks (side-by-side 0-Back, 1-Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 65 publications
(86 reference statements)
3
19
0
Order By: Relevance
“…Twenty-five younger (20–34 years old) and 25 older adults (63–80 years old) participated in the study (see Table 1 for participant characteristics). The sample size was determined on the basis of past related work with similar experimental conditions (Pehlivanoglu et al, 2014 ). The younger adults were students at Birkbeck College and received course credits or a small fee for participating.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five younger (20–34 years old) and 25 older adults (63–80 years old) participated in the study (see Table 1 for participant characteristics). The sample size was determined on the basis of past related work with similar experimental conditions (Pehlivanoglu et al, 2014 ). The younger adults were students at Birkbeck College and received course credits or a small fee for participating.…”
Section: Methodsmentioning
confidence: 99%
“…So far, only one study has systematically varied the task relevance of emotion in an n -back study on aging. Pehlivanoglu et al ( 2014 ) asked younger and older adults to update emotional and neutral faces in an n -back task and to base their decision on either the facial expression, the identity, or on both. Although this design allowed testing (un)binding processes in both age groups, the effects of task-relevant (i.e., expression condition) or task-irrelevant emotion (i.e., identity condition) on updating in the two age groups were not tested.…”
Section: Introductionmentioning
confidence: 99%
“…While the 1-back version of the task primarily taps attentional resources with a simple comparison of the current item with the prior item in the sequence, the 2-back version requires many more operations. For successful performance on the 2-back task, more attentional resources must be allocated to the task and competing responses must be inhibited in order to process, temporarily store, and update constantly changing intervening items (Jonides et al, 2003 ; Pehlivanoglu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Angry faces might have signaled a nonmatch to a greater extent relative to neutral faces because of higher informational value, contributing to faster nonmatch responses rather than more efficient updating in older adults. In contrast, research has shown that older adults have difficulties to unbind task-irrelevant emotional information in an n -back task but only under high load ( Pehlivanoglu, Jain, Ariel, & Verhaeghen, 2014 ), which could be due to the cognitive cost associated with negative material. Szmalec et al (2011) suggested that inefficient (un-)binding during the WM updating process could make participants more susceptible to interference from lures and that controlled recollection processes were needed to reduce this interference.…”
mentioning
confidence: 95%